2017
DOI: 10.1016/j.clim.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic T cell lymphopenia identified in New York State Newborn Screening

Abstract: Quantification of T-cell receptor excision circles (TRECs) for newborn screening for SCID has advanced the diagnosis of severe combined immune deficiency (SCID). However, it has led to the identification of infants with T cell lymphopenia without known cause. The clinical characteristics, appropriate laboratory monitoring, and outcomes of patients remain unclear. We performed a retrospective review of clinical and laboratory studies for 26 infants collected from 7 New York State referral centers from 2010 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 17 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…Many of them recover spontaneously ( 11 ). A recent study by Albin-Leeds et al ( 29 ) has reported that while additional infants with T cell lymphopenia are identified in NBS panels, they seem to do well clinically. Children with severe genetic syndromes often present other, more urgent symptoms at birth.…”
Section: Discussionmentioning
confidence: 99%
“…Many of them recover spontaneously ( 11 ). A recent study by Albin-Leeds et al ( 29 ) has reported that while additional infants with T cell lymphopenia are identified in NBS panels, they seem to do well clinically. Children with severe genetic syndromes often present other, more urgent symptoms at birth.…”
Section: Discussionmentioning
confidence: 99%
“…2,13,14 TRECs count reflects T cell levels and significant benefits have been gained in the diagnosis of SCID by introduction of TRECs in SCID screening programs with high sensitivity and specificity. [15][16][17] Preliminary data from U.S. screening program suggest that 1 of 30,000 to 50,000 infant can have SCID. Our country and such countries with a high rate of consanguineous marriage (Saudi Arabia and Kuwait) data revealed higher numbers than United States.…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible outcomes of patients with ITL. First, the T cell counts may normalize over time, but in our and others experience, the timing of this can vary greatly and may take up to 9 months ( 9 , 20 ). In other cases, the T cell counts may be persistently low and decrease over time, which would necessitate consideration of proceeding to HSCT ( 9 , 20 ).…”
Section: Idiopathic Tcl—a Unique Management Problem For Nbsmentioning
confidence: 98%
“…A number of infants who failed the NBS for SCID are diagnosed with idiopathic T cell lymphopenia (ITL) ( 1 , 9 , 20 ). These patients have low T cell numbers, but not low enough to be considered SCID (>300 autologous T cells/mm 3 ), and lack a genetic diagnosis that results in SCID or a known cause of TCL.…”
Section: Idiopathic Tcl—a Unique Management Problem For Nbsmentioning
confidence: 99%